Síntese e caracterização de géis para cromatografia de exclusão por tamanho via reticulação de Acetato de Celulose com 4,4' - Difenilmetano Diisocianato (MDI) - Rosa, Wesley de Oliveira (Universidade Federal de São Carlos, 2016)
The need to obtain biomaterials in order to reduce environmental impacts has been the focus of research groups in recent years, and cellulose, a dominant component at most forms of plants is a promising resource because of its abundance. In order to improve the ability processing, the chemical modification of cellulose has been widely studied. Among the most important reactions of cellulose are: etherification, esterification, acetylation and oxidation; being cellulose acetate, viscose, nitrocellulose and cellulose ethers, the main cellulose derivatives. The chemical modification with isocyanates presents some unique properties, such as absence of by-products and chemical stability of the urethane group. In this work we were synthesized gels obtained by modified cellulose acetate (CA) with a degree of substitution (DS) 2,5 by crosslinking, with 4,4' - Diphenylmethane diisocyanate (MDI) in stoichiometry of 1:1, in homogeneous by varying the humidity and the homogenization time. For characterization were used the following techniques and tests: vibrational infrared absorption spectroscopy (Fourier Transform Spectrometer - FTIR), size exclusion Chromatography (SEC), molecular absorption spectrophotometry UV-VIS, density determining of the gels by pycnometry, determination of the coefficient swelling, determination of cross-links by Flory-Rehner theory, thermogravimetry (TG) and scanning electron microscopy (SEM). Crosslink density results showed that the gel synthesized in the absence of moisture suffered greater crosslinking with an average number of repeat units between the crosslinking points of about 1000 times lower. The potential applications of these gels were tested, by using than as stationary phase in size exclusion chromatography, having been assessed its efficiency in the fractionation and separation of natural and synthetic polymers. Results showed the effectiveness of the gel as stationary phase on separation of polymers, opening up a range of opportunities, taking into consideration the simplicity of the process and lower costs attributed to it.
Keywords: Celulose; Cellulose; Acetato de celulose; Cellulose Acetate; Cromatografia de exclusão por tamanho; Size exclusion chromatography; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA